Analysis of Self-Efficacy Learning Outcomes on Class VII MTSN 01 Pasuruan Viewed Based On Students' Mathematical Ability - Fariha , Dewi; Rachmatika , Fajriyah (Noumerico: Journal of Technology in Mathematics Education, 2024)
This study aims to analyze self-efficacy's effect on students' learning outcomes in class VII MTsn 01 Pasuruan. This research is a type of descriptive research with a qualitative approach. The main instruments in this study were researchers, and their supporting instruments were diagnostic tests, self-efficacy questionnaires, assignments, and interview guidelines. The subjects in the study were all students of class VII-A MTs Negeri 1 Pasuruan, with three students being selected: one having a high level of self-efficacy, one having a moderate level of self-efficacy, and one having a low level of self-efficacy. The results of this study indicate that the self-confidence variable and mathematics learning outcomes have a significant positive relationship. This means that the higher students' self-efficacy when doing assignments related to mathematics, the better the results of students' learning mathematics. Conversely, if the students' self-efficacy when doing tasks related to mathematics is lower, the students' mathematics learning outcomes will also be lower.